Finding the Sites with Best Accessibilities to Amenities - Lin, Qianlu; Xiao, Chuan; Cheema, Muhammad Aamir; Wang, Wei (Database Systems for Advanced Applications, 2011)
Finding the most accessible locations has a number of applications. For example, a user may want to find an accommodation that is close to different amenities such as schools, supermarkets, and hospitals etc. In this paper, we study the problem of finding the most accessible locations among a set of possible sites. The task is converted to a top-k query that returns k points from a set of sites R with the best accessibilities. Two R-tree based algorithms are proposed to answer the query efficiently. Experimental results show that our proposed algorithms are several times faster than a baseline algorithm on large-scale real datasets under a wide range of parameter settings.